2022
DOI: 10.3389/fnut.2022.883015
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Skeletal Muscle Mass and Severity of Steatosis and Fibrosis in Non-alcoholic Fatty Liver Disease

Abstract: BackgroundSarcopenia is known to be the risk factor of non-alcoholic fatty liver disease (NAFLD). However, studies evaluating the association of skeletal muscle mass (SMM) with liver fibrosis by transient elastography are limited. Here, we investigated the association of SMM with hepatic steatosis and fibrosis assessed in Chinese adults.MethodsPatients who underwent liver ultrasonography at the Health Promotion Center of the First Affiliated Hospital of Nanjing Medical University between January 2020 to June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Similar to our findings, a cross-sectional analysis of 3589 participants from China reported that there was an independent positive association of the android fat ratio and an inverse association of the skeletal muscle index (SMI) with NAFLD defined by the fatty liver index 13. Another study from China conducted by Guo et al , using transient elastography to assess the degree of liver steatosis and stiffness, found that SMI was independently associated with the severity of liver steatosis and fibrosis 14. Shida et al found that NAFLD patients in Japan with a reduced ratio of skeletal muscle mass to visceral fat area had an increased risk of moderate to severe steatosis and advanced fibrosis 12.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our findings, a cross-sectional analysis of 3589 participants from China reported that there was an independent positive association of the android fat ratio and an inverse association of the skeletal muscle index (SMI) with NAFLD defined by the fatty liver index 13. Another study from China conducted by Guo et al , using transient elastography to assess the degree of liver steatosis and stiffness, found that SMI was independently associated with the severity of liver steatosis and fibrosis 14. Shida et al found that NAFLD patients in Japan with a reduced ratio of skeletal muscle mass to visceral fat area had an increased risk of moderate to severe steatosis and advanced fibrosis 12.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have reported that the ratio of skeletal muscle mass to visceral fat area is closely related to the pathophysiology of NAFLD in Korea11 and Japan 12. Previous studies in China have reported the association of android fat and/or skeletal muscle with NAFLD 13 14. However, it remains unclear whether the fat-to-muscle ratio (FMR), a novel assessment of the combined effects of fat and skeletal muscle mass, is associated with the risk of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…The close link between body composition parameters and NAFLD has been investigated. Previous studies have shown that obesity 27 , 28 , visceral adiposity 29 , 30 , and sarcopenia 13 , 31 , are associated with an increased risk for NAFLD. Obesity seems to play a role in both the initial process of simple hepatic steatosis and its progression to advanced liver disease 32 .…”
Section: Discussionmentioning
confidence: 98%
“…The sample is not representative for the study population, which may limit the generalizability of the results. Many variables which may influence the presence of NAFLD were not taken into consideration for this study, such as skeletal muscle mass and comorbidities related to metabolic syndrome including diabetes mellitus, hypertension, and dyslipidemia [ 11 , 19 , 51 ]. So, results must be interpreted cautiously as many confounding variables were not analyzed.…”
Section: Discussionmentioning
confidence: 99%